Differential Regulation of Adhesion and Phagocytosis of Resting and Activated Microglia by Dopamine - Fan, Yang; Chen, Zhilu; Pathak, Janak L.; Carneiro, Ana M. D.; Chung, Chang Y. (Frontiers in Cellular Neuroscience, 2018)
Microglia, the immune competent cells of the central nervous system (CNS), normally exist in a resting state characterized by a ramified morphology with many processes, and become activated to amoeboid morphology in response to brain injury, infection, and a variety of neuroinflammatory stimuli. Many studies focused on how neurotransmitters affect microglia activation in pathophysiological circumstances. In this study, we tried to gain mechanistic insights on how dopamine (DA) released from neurons modulates cellular functions of resting and activated microglia. DA induced the reduction of the number of cellular processes, the increase of cell adhesion/spreading, and the increase of vimentin filaments in resting primary and BV2 microglia. In contrast to resting cells, DA downregulated the cell spreading and phagocytosis of microglia activated by LPS. DA also significantly downregulated ERK1/2 phosphorylation in activated microglia, but not in resting microglia. Downregulation of ERK1/2 by DA in activated microglia required receptor signaling. In contrast, we found a significant increase of p38MAPK activity by DA treatment in resting, but not in activated microglia. These latter effects required the uptake of DA through the high-affinity transporter but did not require receptor signaling. Activation of p38MAPK resulted in the increase of focal adhesion number via phosphorylation of paxillin at Ser83. These results indicate that DA might have a differential, depending upon the activation stage of microglia, impact on cellular functions such as adhesion and phagocytosis.